2004
DOI: 10.1111/j.0303-6987.2004.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of p63, p53, survivin, and hTERT in skin tumors

Abstract: p63 expression may be a marker of basal/progenitor cells and a diagnostic marker in skin tumors. p63 expression is not related to p53 expression in these tumors. This study points to a putative role of survivin and hTERT in the development of certain skin cancers. In addition, our data support the concept of porokeratosis being a premalignant condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 35 publications
9
82
1
4
Order By: Relevance
“…The increased apoptosis in the colonies of untreated hTERT þ cells compared to hTERTÀ cells was unexpected but is in keeping with the increased apoptosis of transformed MIN6 pancreatic cells when grown as three-dimensional clusters rather than monolayers (Luther et al, 2005) and with the apoptosis seen in malignant and even pre-malignant tumours (e.g. Bowen's disease, which is hTERT positive (Park et al, 2004)) compared to their benign counterparts. The lack of increased apoptosis and reduced loss of cell viability in hTERT þ cells after metal treatment emphasizes the link between cell death and telomerase which has been noted in tumours during the development of drug resistance to chemotherapy including metal (cisplatin) (Mese et al, 2001).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 54%
“…The increased apoptosis in the colonies of untreated hTERT þ cells compared to hTERTÀ cells was unexpected but is in keeping with the increased apoptosis of transformed MIN6 pancreatic cells when grown as three-dimensional clusters rather than monolayers (Luther et al, 2005) and with the apoptosis seen in malignant and even pre-malignant tumours (e.g. Bowen's disease, which is hTERT positive (Park et al, 2004)) compared to their benign counterparts. The lack of increased apoptosis and reduced loss of cell viability in hTERT þ cells after metal treatment emphasizes the link between cell death and telomerase which has been noted in tumours during the development of drug resistance to chemotherapy including metal (cisplatin) (Mese et al, 2001).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 54%
“…Lack of caspase 3 resulted in increased proliferation and decreased differentiation of embryonic keratinocytes 36. However, the possible involvement of this pathway in CSCC remains to be clarified, although increased expression of survivin, an apoptosis inhibitor targeting caspase 3 and caspase 7, was observed in CSCC tumors 37, 38, 39.…”
Section: Notch Signaling In Cutaneous Squamous Cell Carcinoma (Cscc)mentioning
confidence: 99%
“…In our system using human papillomavirus (HPV)16 E6/7 immortalized keratinocytes (KC), we found that the immortalized cells mimicked AK in that, while p53 and Rb pathways were blocked and hTERT was constitutively expressed (Park et al, 2004), the cells were exquisitely sensitive to UVB apoptosis compared to primary KC from which they were derived (Simbulan-Rosenthal et al, 2002). We further found that this sensitivity was due in part to downregulation of Bcl2, which resulted in the activation of caspases-9 and -3 at much lower doses of UVB (Simbulan-Rosenthal et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, the rates of AK progression to SCC are much lower, with rate estimates of 0.2% (Marks et al, 1986), 0.1% (Marks et al, 1988), and 0-1.1% per year (Frost et al, 2000). While the exact details are yet to be elucidated, an insight into the molecular mechanisms of AK regression can be gleaned from studies in which expression of immortalizing and survival proteins were examined in normal skin, porokeratosis, AK, SCC in situ, and invasive SCC (Park et al, 2004). Interestingly, the majority of premalignant lesions, like the malignant lesions, demonstrated stable expression of hTERT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation